Does Political Connection Affect Corporate Debt Financing-Empirical Evidence from China’s Capital Market? - Keping Wu (Forest Chemicals Review)
Using the data of Chinese private listed companies, this paper examines the effect of creditor rights protection of politically connected enterprises on the scale of debt financing, the structure of debt financing, maturity structure of debt financing, debt financing costs from both micro and macro fundamentals. We find that the higher level of creditor rights protection of politically connected enterprises, the larger the scale of corporate debt financing; the higher level of creditor rights protection of politically connected enterprises, the higher level of leverage; the higher level of creditor rights protection of politically connected enterprises, the greater proportion of long-term liabilities to total liabilities; the higher level of creditor rights protection of politically connected enterprises, the lower cost of debt financing. The research results show that establishing political connections and improving the protection of corporate creditor’s rights is conducive to rational allocation of resources, alleviating the problem of insufficient corporate financing, and promoting the healthy development and orderly operation of China’s economy under the new normal.